+0  
 
0
297
1
avatar

What is b when (2x + a)(x +3) = 2x squared + 4 ax + b

 Sep 10, 2017
 #1
avatar+98141 
+1

(2x + a)(x +3) = 2x^2 + 4 ax + b

 

Expand the left side

 

2x^2 + ax + 6x + 3a  =  2x^2 + 4ax  + b      subtract  2x^2  from both sides

 

ax + 6x + 3a  =  4ax + b        simplify

 

(a + 6)x +  3a  =  (4a)x + b

 

This implies that

 

a + 6  = 4a    →   6 = 3a  →  a = 2

 

And......

 

3a  = b

3(2)   =  b  =  6

 

 

cool cool cool

 Sep 10, 2017

20 Online Users

avatar
avatar
avatar
avatar
avatar